Pengembangan Model Project Based Learning (PjBL) Berbantuan Augmented Reality (AR) untuk Meningkatkan Keterampilan Proses Sains dan Sikap Ilmiah Peserta Didik Kelas XI pada Materi Struktur Sel - Indriani, Ratna; Wahidin, Wahidin; Arif, Asep Ginanjar (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
Developments in the field of education in the industrial era 4.0 demanded a change in students' perspectives on the quality of learning such as learning in biology subjects. Biology learning can foster students' thinking skills to solve everyday problems through observation and observations that are based on a scientific attitude and can develop scientific process skills. To achieve this, it is necessary to choose the right model. Student-centered models such as project based learning are very suitable for today's learning supported by adequate technology and increase student learning interest such as augmented reality. This study aims to see an increase in science process skills and scientific attitudes of students from the development of augmented reality-assisted project based learning models. The research method with the ADDIE development model and the type of research and development research. The research instrument consisted of interviews, observations and tests, the population of all students in class XI IPA and samples XI IPA 1, XI IPA 3. The results showed that for KPS the average pretest score for the experimental class was 49.9 and the average posttest score was 80.5 while in the control class the average pretest score was 48.7 and the posttest average score was 60 and for scientific attitude the average experimental pretest score was 60, the posttest was 86.9 while the control class averaged the pretest score was 58.9 posttest was 81. Followed by analysis t test and obtained a sig(2-tailed) value of 0.000<0.05, so it was concluded that the development of the AR-assisted PjBL model can improve KPS and scientific attitudes of students. The recommendation from this research is that this project-based learning model manual is used to improve problem-solving skills in different materials.